Evolução molecular e padrões macro e micro evolutivos em Drosophila incompta (Diptera, Drosophilidae) - De Re, Francine Cenzi (2016)
The flavopilosa group was proposed by Wheeler and colleagues in 1962. In taxonomic terms, it seems to be a monophyletic group, belonging to virilis-repleta radiation of the Drosophila subgenus. However, the exact position of the group within that radiation is still under discussion and there is wide incongruence between different markers. According to the classification proposed to date, the flavopilosa group is divided into two subgroups, nesiota and flavopilosa, comprising a total of 16 species plus Drosophila incompta, model organism of this thesis. D. incompta is strictly adapted to the exploitation of the Cestrum flowers, both as oviposition sites, and as a substrate for larval development. For this, this species has developed a number of unique phenotypic adaptations that facilitate the exploitation of this resource. Furthermore, it is believed that D. incompta presents a series of molecular adaptations regarding their ecological specialization, and this must be reflected particularly in the gene set of olfactory and gustatory receptors. Also because of their limited ecological patterns, the distribution of D. incompta is completely dependent on the distribution of their hosts, who seem to be abundant in the Neotropics. In Brazil, specifically, the plants of Cestrum genus are distributed over the Biomes Cerrado and Atlantic Forest, two vegetation formations which have changed considerably in the glacial and interglacial periods of the Quaternary. In fact, climate fluctuations that period, marked by the reduction of temperature and humidity in the Southern Hemisphere appear to have caused contractions in the distribution of the Atlantic Forest and its replacement by other, consistent climate, such as the Cerrado and Caatinga. Given the complexity of macro, microevolutionary and molecular scenarios involving D. incompta, the general aim of this thesis is to characterize the phylogenetic, phylogeographic and molecular aspects associated with ecological specialization of D. incompta to the flowers of the Cestrum. For this, we characterize the mitochondrial genome of D. incompta, infer its correct phylogenetic position from phylogenomic data, identifying possible sources of incongruity, characterized the gene repertoire of ORs and GRs and analyze their patterns of diversity and structuring throughout Southern Brazil. Our results show that the mitochondrial genome of D. incompta shows perfect synteny with the other species of the genus Drosophila, consisting of 13 protein-coding genes, 22 tRNAs, 2 rRNAs and a A-T rich region. Besides, polymorphism analysis over this genome indicate the presence of pronounced levels of intra-specific diversity. Regarding the phylogenetic position, it was demonstrated that while the mitochondrial genome supports the clade formed by D. incompta and D. mojavensis, the nuclear genes recover D. incompta and D. virilis as sister species. As, in general, these positions are maintained even when the effects of saturation are controlled, it is believed that the incongruity between the two data sets must be a reflection of differences in their evolutionary histories. Regarding the repertoire of ORs and GRs, we find 28 and 12 genes belonging to each of these families in the genome of D. incompta, respectively. The reduction in the number of genes relative to other species of Drosophila appears to be adaptative due to restricted ecological pattern. Still, these genes appear to be under effect of purifying selection. Finally, the phylogeographic analysis shows that populations of D. incompta of southern Brazil experienced a population expansion event between 175 and 100 thousand years ago followed by a period of stability that extends to the present day levels of diversity and the lack of a geographic pattern of genetic structure seem to reflect the occurrence of high levels of gene flow in the species, in response to changes in the abundance and availability of the resources exploited.